Visible light responsive titania photocatalysts codoped by nitrogen and metal (Fe, Ni, Ag, or Pt) for remediation of aqueous pollutants - Sun, Hongqi; Zhou, Guanliang; Liu, S.; Ang, Ha-Ming; Tade, Moses; Wang, Shaobin (Elsevier BV, 2013)
Various cation and nitrogen doped and codoped TiO2 photocatalysts, such as N–TiO2, Pt–TiO2, N–Fe–TiO2, N–Ni–TiO2, N–Ag–TiO2 and N–Pt–TiO2, were prepared by an acid-catalysed sol–gel process. The photocatalysts were characterised by X-ray diffraction (XRD), nitrogen adsorption–desorption isotherms, UV–visible diffuse reflectance absorption spectroscopy (UV–vis DRS), and X-ray photoelectron spectroscopy (XPS). The activities of the photocatalysts were evaluated in photodegradation of phenol solutions under simulated sunlight irradiations. A negative effect of some transition metals (iron and nickel) onphotocatalysis was observed on N-metal codoped TiO2, while enhancements in photocatalysis from noble metals (silver and platinum) were obtained. N–Pt codoped TiO2 showed a higher activity under UV–vis irradiations than Degussa P25, with an enhancement of 5.9 times higher. The synergistic effect of N–Pt-codoping was ascribed to the multivalent states of platinum. In addition, photocatalytic activity of N-, Pt-doped and N–Pt-codoped materials were further investigated under visible light irradiations with lambda > 430 nm and lambda > 490 nm. This study therefore demonstrated a promising strategy for design of highly efficient photocatalysts for remediation of aqueous pollutants.